Waste Management Strategy of Agricultural Enterprises to Improve the Efficiency of Rural Development - MAKHMETOVA, Dana; TLESSOVA, Elvira; NURKENOVA, Makpal; AUELBEKOVA, Aigul; ISSAYEVA, Bibigul (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023, 2023)
In the context of modern trends in the greening of the economy, sustainable development, changes in the structure of agricultural production, and the situation that has developed in Kazakhstan with the accumulation, utilization, and disposal of waste, the issues of agricultural waste management remain relevant and require further scientific research and sound practical solutions. The purpose of the article is to form strategic directions for waste management of agricultural enterprises, where the main place is occupied by effective waste management in the context of crop production, animal husbandry, animal tissue, and agrochemical waste . The article presents the principles of a Waste Management Strategy of agricultural enterprises, and a tree of objectives of the Strategy of agricultural enterprises is formed. The features of effective management of agricultural waste, including plant and animal waste, and directions for effective management of agrochemical waste are determined. Reduction of soil and groundwater pollution in the implementation of effective waste management of agricultural enterprises, as well as measures to minimize the formation of agricultural waste, are summarized. The main measures in state incentives for the effective management of agricultural waste are identified .